Two-dimensional simulation of quantum reflection - Galiffi, Emanuele; Sünderhauf, Christoph; DeKieviet, Maarten; Wimberger, Sandro (Journal of physics. B, Atomic, molecular and optical physics, 2017)
A propagation method for the scattering of a quantum wave packet from a potential surface is presented. It is used to model the quantum reflection of single atoms from a corrugated (metallic) surface. Our numerical procedure works well in two spatial dimensions requiring only reasonable amounts of memory and computing time. The effects of the surface corrugation on the reflectivity are investigated via simulations with a paradigm potential. These indicate that our approach should allow for future tests of realistic, effective potentials obtained from theory in a quantitative comparison to experimental data.